Apakah investor berpeluang mengalahkan pasar Indonesia? - Budiarso, Novi Swandari; Pontoh, Winston (Yayasan Widyantara Nawasena Raharja, 2023)
Since 2020, the capital market in Indonesia has been filled with information about changes in global conditions which have greatly influenced economic conditions. This study aims to estimate market efficiency (in weak form) using time series data from 1 January 2020 to 15 December 2023. The findings show that market conditions throughout the observation period were inefficient in weak form. Apart from that, the findings also show that the risk-return tradeoff of the estimated market index in Indonesia tends to improve. However, the movement pattern of the estimated market index is also predicted to remain in an inefficient condition in a weak form. These findings imply that investors tend to have the opportunity to beat the market in the next 150 days with the aim of obtaining abnormal returns.